Analysis of non-active power in non-sinusoidal circuits using geometric algebra. (March 2020) - Montoya, Francisco G.; Baños, Raúl; Alcayde, Alfredo; Arrabal-Campos, Francisco M.; Viciana, Eduardo
Highlights: Geometric algebra framework is applied to solve non sinusoidal and nonlinear circuits. A new definition of non-active power based on geometric algebra is presented. New current decomposition is introduced to minimize line looses and supply active power. This new method is validated through some examples with linear and non-linear loads. Abstract: A new approach for the definition of non-active power in electrical systems is presented in this paper. Through the use of geometric algebra, it is possible to define a new term called geometric non-active power, which is applicable to both sinusoidal and non-sinusoidal systems, and to both linear and nonlinear loads. The classic definitions of distortion and reactive power are compared and discussed in our proposal. We verify how geometric non-active power can appear in both purely resistive and purely reactive systems. The superiority of geometric algebra is revealed through several examples of electrical circuits previously analysed in specialised literature. Furthermore, a new geometrical current decomposition is proposed, for the first time, to provide a greater physical sense to existing geometric power. The results obtained confirm that classic concepts based on apparent power S are based on a lack of physical meaning, which is why geometric algebra theory should be adopted instead.